The relationship of treatment type and epithelial / subepithelial changes in healed dudenal ulcers - Melih ÖZEL,; Levent DEMİRTÜRK,; Ahmet Kemal GÜRBÜZ,; Ergun UÇMAKLI,; Yusuf YAZGAN,; Mehmet DANACI, (Turkish Journal of Gastroenterology, 2019)
-